Tensile Properties of Friction Stir Welds of AA 7020 Aluminum Alloy - Heidarzadeh, Akbar; Barenji, Reza Vatankhah; Esmaily, Mohsen; Ilkhichi, Atabak Rahimzadeh (Springer India, 2015)
In this investigation, response surface methodology was used to predict and optimize the tensile properties of friction stir welded AA 7020 aluminum alloy. Tensile properties, microstructural features and fractography of the joints were measured and investigated using tensile test, optical and scanning electron microscopes, respectively. In addition, the influences of friction stir welding parameters on tensile properties of the joints were examined thoroughly. The results revealed that with increasing the heat input, the tensile strength of the joints increased up to a maximum value and then decreased, where the elongation of the joints increased continuously. Moreover, the optimal condition to obtain a maximum of tensile strength was 1,055 rpm, 97 mm/min and 7.4 kN, where as for tensile elongation was 1,320 rpm, 72 mm/min and 7 kN.
Keywords: Friction stir welding; Tensile strength; Elongation; Modeling